MIDDLE EASTERN CRAFTS: YESTERDAY, TODAY, TOMORROW, VICTORIA & ALBERT MUSEUM, OCTOBER 11-12, 2018 - Mc Sweeney, Anna (My University, 2020)
Craft is having a moment – the international market for contemporary craft is more buoyant than ever, with record trade figures and increasingly high-profile exhibitions and publications.1 But contemporary craft from the Middle East is not equally represented in this global turn. Middle East artists and galleries did not feature among the 2018 or 2019 finalists for the prestigious Loewe and Collect craft prizes. The work of the intrepid curator Mariam Rosser-Owen at the Victoria & Albert Museum (V&A) will go some way towards restoring the reputation and visibility of craftsmanship from the region. In 2015 she won a New Collecting Award from the Art Fund that has allowed her to focus on contemporary craft from North Africa, an award that led to her organization of the conference Middle Eastern Crafts: Yesterday, Today and Tomorrow that took place at the V&A in October 2018.
MIDDLE EASTERN CRAFTS: YESTERDAY, TODAY, TOMORROW
PUBLISHED
Keywords: Islamic art; Middle Eastern Art; craft